Instructional Strategies in Mathematics Learning for Developing Students’ 4C Abilities: A Literature Review - Ahyani Mirah Liani (International journal of technology and education research, 2026)
In the 21st century, students are expected to master the 4C skills: creativity, critical thinking, communication, and collaboration, in order to remain competitive in a globalized world. However, the integration of these skills into mathematics learning, particularly within the context of Islamic education, remains suboptimal. This study aims to identify and analyze mathematics learning strategies that enhance students' 4C skills through a systematic literature review. The research employed the PRISMA method to guide the selection of relevant articles. A total of 47 articles published between 2016 and 2025 were initially identified from the Google Scholar database, and 15 met the inclusion criteria for final analysis. The review found that Project-Based Learning (PjBL), Problem-Based Learning (PBL), STEM approaches, and other innovative strategies significantly contribute to the development of students' 4C competencies. These strategies foster active engagement, encourage creative and critical problem-solving, and enhance both communication and collaboration in mathematics learning. The findings emphasize the importance of adopting more student-centered learning models that support the development of 4C skills. This study offers valuable insights for curriculum developers and educators in designing effective mathematics instruction that equips students to face global challenges.